(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aims to apply the necessary professional care and skill standard issued by the American Institute of Internal Auditors (IIA) within the categories of internal auditing attributes standards and its elements, and to demonstrate the importance of this standard in improving the quality of internal auditing and its reflection on the external auditor’s procedures, for the purpose of reducing the risks of financial and administrative corruption, and for the purpose of achieving the objectives of For the research, a two-axis survey list was designed that included many questions directed to workers in the Internal Audit Division in a community. The research sample was a survey list distributed to them directly. The response rate was (96%) from the sample, which amounted to (61) auditors, and statistical analysis was done. According to the (SPSS) program, the results of the research showed a relative application of the standard of skill and professional care necessary for internal auditing to reflect positively on the procedures of the external auditor, with the aim of proving the research hypothesis in applying the standard of skill and professional care necessary for internal auditing to the research sample, and the researcher reached a number of conclusions. The most important of which is that applying the necessary professional skill and care standard and its elements improves the quality of internal auditing in the economic unit sample of the research and thus reflects positively on the external auditor’s procedures. The researcher also presented a set of recommendations, the most important of which is the necessity of keeping pace with developments that have occurred in internal auditing, and working to apply the skill and professional care standard. Necessary in the research sample, for the purpose of improving the quality of internal auditing.